Bilateralizing multilateral aid? Aid allocation by World Bank trust funds - Vera Eichenauer; Stephen Knack (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
Over the last decade, donors of foreign aid quadrupled their annual contributions to trust funds at the World Bank. Concerns have been raised that trust fund aid may undermine the incentives associated with IDA s performance-oriented aid allocation. Moreover, the earmarking of contributions to donors preferred recipient countries might bilateralize multilateral aid, potentially to the detriment of aid effectiveness. Using new data on World Bank trust fund disbursements for the 2002-2012 period, we test whether trust fund aid substitutes for IDA inflows, and, as official narratives suggest, for other aid inflows. We also investigate the bilateralization hypothesis by comparing multilateral core aid to trust fund disbursements. Trust fund aid is generally not allocated according to World Bank s Country Policy and Institutional Assessment (CPIA) index, which could undermine the incentives generated of the IDA allocation mechanism. This result is confirmed when we consider the health, education, and environment sector separately using sector-specific CPIA scores and IDA aid. We do not find systematic evidence that trust funds are to a larger degree motivated by political and economic motives.
Keywords: F55; O19; P45; 330